Comparison of Smith-Petersen Osteotomy Versus Pedicle Subtraction Osteotomy Versus Anterior-Posterior Osteotomy Types for the Correction of Cervical Spine Deformities. Issue 3 (1st February 2015) - Kim, Han Jo; Piyaskulkaew, Chaiwat; Riew, K. Daniel
<x xml:space="preserve">Abstract</x> Study Design. Retrospective case controlled study. Objective. To describe the amount of correction obtained with different types of osteotomies in the cervical spine when treating cervical deformity. Summary of Background Data. Although the corrective power of various osteotomies in the thoracic and lumbar spine are well described, there are no reports in the literature on the corrective capabilities of osteotomies in the cervical spine to guide preoperative planning for cervical and cervicothoracic deformities. Methods. Patients who underwent cervical osteotomies for cervical deformity were identified in a 10-year period from 2000 to 2010. Demographics, surgery type, osteotomy type (Smith-Petersen Osteotomy [SPO], pedicle subtraction osteotomy [PSO], anterior-osteotomy [ATO]), operative details, and radiographs were collected for preoperative and ultimate postoperative time points. Cervical lordosis and basion plumb line were collected to assess angular and translational corrections. Results. A total of 61 patients had surgery for cervical deformity in the study period. The mean angular correction generated through 1 SPO was 10.1° per level (range, 1.0°–24.9°/level) and the mean translational correction was 1.8 cm (range, 0.5–4.0 cm/SPO). A PSO generated a mean angular correction of 34.5° (range, 28.2°– 80.0°/level, maximum 1/case) per PSO and translational correction of 2.5 cm per PSO (range, 0.2–5.6 cm). An ATO generated a mean angular correction of 17.1° per osteotomy (range, 3.5°–32.1°/level) and translational correction of 1.0 cm per osteotomy (range, 0.1–3.0 cm/level; total, 0.5–3 cm). Combined ATO and SPO with posterior cervical fusion generated a mean angular correction of 27.8° per osteotomy (range, 3.7°–66.7°/level) and translational correction of 2.6 cm per osteotomy (range, 0.2–7.0 cm/level). Conclusion. Posteriorly based osteotomies provided better translational correction than ATOs. The angular correction achieved by 1 PSO was similar to ATO + SPOs. ATO + SPOs provided equal or better corrections than isolated PSOs, with equal length of stay and less estimated blood loss. Level of Evidence: 4